The impact of monetary instruments on shock absorption in EU-Countries - Claudia Müller; Herbert S. Buscher (Zentrum für Europäische Wirtschaftsforschung (ZEW), 1999)
The main characteristic of the implementation of the European Monetary Union (EMU) is the transition from various national currencies to the Euro, the common European currency. A final fixing of the individual bilateral exchange rates of all European countries involved in the Monetary Union accompanies this step. Regarding the microeconomic effects, a positive impact on trade is expected by the reduction of transaction and foreign currency management costs as well as by the elimination of the exchange rate uncertainty. Formerly, the latter influenced foreign trade.1 At the same time, however, the autonomy of national economic policy is restricted by the loss of former national monetary policy instruments, which will now operate European-wide with the start of EMU. In addition to a unique interest rate policy inside EMU, there will be no longer an – even limited - flexibility of the nominal exchange rates. According to the theory of Optimal Currency Areas (OCA)2, in a flexible or at least not irrevocably fixed exchange rate system3 these are two potential instruments carrying some of the burden of macroeconomic adjustment. EMU supporters and sceptics give these aspects different values: while supporters hope to obtain growth and employment impulses through more monetary stability, sceptics are anxious, since in their opinion, the economic convergence4 of the European states is yet not optimal and, additionally, alternative instruments do not yet function efficiently.
Keywords: E65; E30; E10; F15; 330; European Monetary Union; Shock Absorption; Monetary Instruments; Geldpolitik; Zinspolitik; Währungspolitik; Konjunkturpolitik; Schock; Konjunkturzusammenhang; Schätzung; Österreich; Niederlande; Frankreich; Italien; Großbritannien; Deutschland